Dental Care Utilization among Veterans by Smoking Status - R. Constance Wiener; Ruchi Bhandari; Alcinda K. Trickett Shockey; Christopher Waters (Hindawi Limited, 2019)
Background. Given the critical importance of dental care utilization among veterans and the overall health consequences of tobacco use in all populations, the purpose of this research is to examine smoking as a risk factor for poor dental care utilization among United States Veterans. Methods. A secondary data analysis of cross-sectional data from the National Survey of Veterans was conducted. The primary outcome was dental care utilization (Yes, No). Frequency, chi-square analyses, and multivariate logistic regression statistical tests were performed while adjusting for confounding factors. Results. There were 6,308 veterans in the study. Veterans who were current smokers were less likely to have dental care utilization within the previous six months than former smokers or never smokers. In unadjusted logistic regression analysis, current smokers had an odds ratio of 2.83 [95% CI: 2.36, 3.40] as compared with never smokers. The adjusted odds ratio for current smoking on dental care utilization was 1.71 [95% CI: 1.40, 2.09] as compared with never smoking. Conclusions. Since veterans who smoked are less likely to have dental care utilization within the previous six months, they are at higher risk for later diagnosis of dental problems. Veterans who smoke should be specifically targeted with interventions to ensure frequent dental visits, so future problems may be averted or managed early in their development.